Low cost wind turbine coasting system / \c Jong Sze Bui - Jong Sze Bui (School of Electrical Engineering, University Malaysia Perlis, 2011)
In this project, the main focus is to design a system to sense the direction of the wind and tune the turbine towards the wind direction. A conventional wind turbine faces towards the wind direction through the tail behind of the turbine.